Protein-sparing effect with high energy levels and obtaining the optimum digestible energy/digestible protein ratio in growth diets to Oreochromis niloticus(L.) - Gutierrez, Felix Walter (2013)
The sparing effect of the dietary protein using diets with high energy levels was evaluated. A factorial design was used to examine the interaction of two levels of protein (30 and 35%) and two levels of digestible energy (3.3 and 3.7 kcal/g) on the weight gain (WG), food conversion FC), retained protein (PR), retained energy (ER) and protein efficiency ratio (PER) in “sex reversal Nile tilapia” (Oreochromis niloticus). Diets contained anchovy and soybean meal as protein sources and yellow corn and wheat bran as energy sources. The fish oil was used to adjust the energy levels. There were highly significant interactions (P<0.01) between the experimental diets. In diets with 30% proteins, the increase of digestible energy significantly enhances WG, FC, PR, ER and PER, where the level of 3.7 kcal/g had the best performance. With 35% protein, the increase of digestible energy had not significant influence on the GP, CA, PR, ER and PER, however the growth of sex reversal Nile Tilapia was improved with the level of 3.3 kcal/g. When were compared both diets, were not find significant differences. Considering the protein cost, it can be concluded that best response was obtained with a diet containing 30 % of protein and 3.7 kcal/g of digestible energy and optimum digestible energy/ digestible protein ratio of 13.75 kcal/g protein.